(untitled) (Experimental biology, 2015)
In the article was studied the effect of inoculation endomycorrhizal fungi of Glomus ( G. etunicatum Becker et Gerdemann, G. intraradices Schenck et Smith, G. claroideum Schenck et Smith.) and microalgae (Chlorococcum sp., Anabaenopsis sp., Anabaena cylindrospora, Anabaena laxa, Pseudoanabaena sp.) the growth of seedlings, dry weight, protein content, nitrate reductase activity of 45-day plant wheat (Triticum aestivum L.) varieties of Bogarnaya 56. It is shown that the use of microalgae A. laxa and Pseudoanabaena sp. is perspective for creating algo-, mycobionts associations, because these species have a positive influence on physiological and biochemical parameters of wheat in the laboratory.